2013
DOI: 10.1002/ca.22301
|View full text |Cite
|
Sign up to set email alerts
|

The fibular collateral ligament of the knee

Abstract: The fibular collateral ligament (FCL) is one of the larger ligaments of the knee. The FCL, along with the popliteus tendon, arcuate popliteal ligament, and joint capsule, make up the posterolateral corner of the knee. Recently, there has there been an increased awareness and research on the structures of the posterolateral corner of the knee, particularly the FCL. Studying the detailed structure of the FCL may provide a better understanding that can lead to better diagnosis and treatments following injury. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Regarding the presence and form of bursa, the cases were evaluated in four types as absent, sac form lying superficial to LCL, vagina synovialis form and bursa lying deep to LCL. Even though the presence of a LCL-biceps femoris bursa was mentioned (LaPrade & Hamilton, 1997; Brinkman et al; Espregueira-Mendes & da Silva; Song et al, 2014) a vagina synovialis which embraced superficial, anterior and deep surfaces of the distal part of LCL has not been mentioned enough in the literature, except one (Fig. 3b).…”
Section: Lateral (Fibular) Collateral Ligamentmentioning
confidence: 99%
“…Regarding the presence and form of bursa, the cases were evaluated in four types as absent, sac form lying superficial to LCL, vagina synovialis form and bursa lying deep to LCL. Even though the presence of a LCL-biceps femoris bursa was mentioned (LaPrade & Hamilton, 1997; Brinkman et al; Espregueira-Mendes & da Silva; Song et al, 2014) a vagina synovialis which embraced superficial, anterior and deep surfaces of the distal part of LCL has not been mentioned enough in the literature, except one (Fig. 3b).…”
Section: Lateral (Fibular) Collateral Ligamentmentioning
confidence: 99%
“…Recent clinical and cadaveric studies have demonstrated the complexity of biceps femoris tendon insertion, showing it has both medial and lateral slips (each with an anterior and posterior component) as well as attachments into the lateral condyle of the femur, the popliteus tendon and the arcuate popliteal ligament. [1][2][3] This may explain the important role of the biceps femoris tendon in adding dynamic stability to the posterolateral corner by means of its numerous attachment sites.…”
Section: Introductionmentioning
confidence: 99%